Characterization of the complete plastome of Saposhnikovia divaricata (Turcz.) Schischk - Li, Lingli (Mitochondrial DNA B Resour, 2020)
Saposhnikovia divaricata is traditional herbal medicine with a long history in China. We reported the complete chloroplast genome of S. divaricate using the next generation sequencing. A total of 115 unique genes were annotated, consisting of 81 protein coding genes, 30 tRNA and 4 rRNA. The overall AT content was 69.2%. The molecular phylogenetic tree reveals that S. divaricate is closely related to Peucedanum in tribe Selineae.